2017
DOI: 10.1016/j.jcrc.2017.07.030
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-dose furosemide in critically ill patients with early acute kidney injury: A pilot randomized blinded controlled trial (the SPARK study)

Abstract: ClinicalTrials.gov Identifier: NCT00978354 registered September 9, 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 43 publications
2
60
0
Order By: Relevance
“…In regard to rates of hypernatremia, providers were permitted to request continuation of furosemide despite elevated sodium levels, likely resulting in the subsequent increased rate of metolazone use in the intervention group. There was a significant difference in cumulative fluid balance that was likely due to higher furosemide exposure in the intervention group, as demonstrated in previous protocols of furosemide in acute kidney injury [10]. The significant increase in episodes of hypernatremia and hypokalemia are predictable and reversible within this strategy.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In regard to rates of hypernatremia, providers were permitted to request continuation of furosemide despite elevated sodium levels, likely resulting in the subsequent increased rate of metolazone use in the intervention group. There was a significant difference in cumulative fluid balance that was likely due to higher furosemide exposure in the intervention group, as demonstrated in previous protocols of furosemide in acute kidney injury [10]. The significant increase in episodes of hypernatremia and hypokalemia are predictable and reversible within this strategy.…”
Section: Discussionmentioning
confidence: 60%
“…Previous protocols guiding volume removal in the critically ill can be found in specific populations including acute decompensated heart failure, AKI, or RRT weaning, with protocolized approaches often improving clinical outcomes versus standard of care [9][10][11]. Further, while limited evidence is available steering diuretic deresuscitation in the broad ICU population, protocols have relied upon dated monitoring parameters, including central venous or pulmonary artery occlusion pressures [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Current guideline recommends defining AKI based on serum creatinine (SCr) increase and oliguria, and staging AKI by the worse of the two parameters [7]. To explore the effect of diuretics on outcomes of AKI, studies often included patients using both UO and SCr criteria [2,8]. However, Kellum and colleagues in a study of 23,866 AKI patients found that the mortality of patients with AKI defined by UO criteria was much lower than those staged according to both UO and SCr criteria [9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, automated matched hydration systems using diuretics and fluids together exist for the prevention of contrast-associated AKI (CA-AKI). While some authors found a reduction in the incidence of CA-AKI [5], studies in patients with AKI did not demonstrate a beneficial effect on progression of AKI [6]. In general, fluids should be considered as therapy for patients with intravascular hypovolaemia and diuretics should be reserved for patients with intravascular hypervolaemia.…”
Section: Myth #1mentioning
confidence: 98%
“…However, frusemide has no direct effect on chances of renal recovery. A pilot trial (the SPARK study) compared low-dose frusemide versus placebo in patients with early AKI and found no difference in the rate of worsening AKI or need for RRT [6].…”
Section: Myth #7mentioning
confidence: 99%